Development of E-Learning Assisted Biology Learning Media on Excretion Material in Class XI at SMA Negeri 1 Maesaan - Paulus Exel Poli; Dientje F. Pendong; Metilistina Sasingga (International Forum of Researchers and Lecturers, 2023)
This research aims to develop Biology learning media and determine the feasibility and response of students to E-Learning learning media at SMA Negeri 1 Maesaan, Maesaan District. Data was collected using interviews and questionnaires and then analyzed using quantitative methods with a descriptive analysis approach. Based on the research results on